Two-dimensional alkyne-imine covalent organic framework material for water vapor adsorption and preparation method thereof

CN122234328BActive Publication Date: 2026-10-09DONGHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610686167.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-19
Publication Date
2026-10-09
Estimated Expiration
2046-05-19

AI Technical Summary

Technical Problem

[0004]本发明所要解决的技术问题是提供一种用于水蒸气吸附的二维炔基-亚胺共价有机框架材料及其制备方法,以克服现有技术中二维共价有机框架层间堆叠模式难以精准调控、材料结晶性与结构稳定性不足以及大气集水性能有待提升等问题

Benefits of technology

[0030] (1) This invention achieves the precise construction of a two-dimensional alkynyl-imine covalent organic framework by introducing a benzo[c][1,2,5]thiadiazole unit with a strong dipole moment into a two-dimensional alkynyl-imine covalent organic framework material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122234328B_ABST
    Figure CN122234328B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of two-dimensional alkyne-imine covalent organic framework materials for water vapor adsorption and its preparation method, to aromatic diamine monomer and aromatic aldehyde monomer as building unit, synthesis by Schiff base condensation reaction.The present application proposes a kind of strategy based on dipole-dipole interaction, realizes the accurate construction of two-dimensional alkyne-imine covalent organic framework.The prepared material shows excellent crystallinity and chemical stability, and exhibits good adsorption performance and cyclic stability in water vapor adsorption process, and shows the potential application prospect in atmospheric water collection field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of atmospheric water collection technology, and specifically relates to a two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption and its preparation method. Background Technology

[0002] With the combined effects of population growth, accelerated industrialization, and environmental changes, the global freshwater shortage is becoming increasingly severe, making the development of sustainable unconventional freshwater acquisition technologies a crucial research direction. The widespread presence of water vapor in the atmosphere provides a potential source of freshwater, thus atmospheric water harvesting technology has attracted widespread attention due to its independence from traditional surface and groundwater distribution limitations. Compared to methods such as mist collection and direct condensation, adsorbent-based atmospheric water harvesting technology leverages adsorption-desorption processes to achieve efficient enrichment and controlled release of atmospheric moisture. This not only broadens its applicability but also allows for stable operation in low-humidity environments, demonstrating promising applications in the development of unconventional freshwater resources.

[0003] As a novel type of crystalline porous material, two-dimensional covalent organic frameworks (2D COFs) possess broad application prospects in gas adsorption and separation, catalysis, sensing, and energy storage due to their advantages such as high designability, tunable pore size, large specific surface area, ordered channels, and absence of metal components. By rationally selecting aromatic aldehydes and aromatic amine monomers, the pore size, framework polarity, hydrophilicity / hydrophobicity, and interlayer interactions of imine-linked 2D COFs can be precisely controlled, thereby affecting their water vapor adsorption performance and structural stability. Furthermore, introducing alkyne units into 2D COFs materials can expand the π-conjugated system, regulate the pore environment, and enhance framework order. It is worth noting that the interlayer interactions between adjacent layers in 2D COFs materials are dominated by non-covalent interactions, and the precise control of their stacking mode still faces challenges. Therefore, developing two-dimensional alkyne-imine covalent organic framework materials with well-defined framework structures, high crystallinity, and excellent water vapor adsorption performance, and establishing efficient preparation methods, is of great significance for expanding the application of this type of material in atmospheric water collection and other fields. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption and its preparation method, so as to overcome the problems of the existing technology, such as the difficulty in accurately controlling the interlayer stacking mode of two-dimensional covalent organic frameworks, insufficient material crystallinity and structural stability, and the need to improve atmospheric water collection performance.

[0005] This invention provides a two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption, the general structural formula of which is:

[0006] , At least one of them; wherein, R 1 R 2 R 3 R 4 R 5 Each atom is independently selected from one of hydrogen, alkyl, alkoxy, hydroxyl, or halogen atoms; X is independently selected from one of oxygen, sulfur, or selenium atoms.

[0007] This invention also provides a method for preparing a two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption, comprising the following steps:

[0008] Aromatic diamine monomers and aromatic aldehyde monomers are reacted via Schiff base reaction to obtain the aforementioned two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption, such as... Figure 3 As shown.

[0009] Preferably, the general structural formula of the aromatic diamine monomer is as follows: R 1 R 2 Each atom is independently selected from one of hydrogen, alkyl, alkoxy, hydroxyl, or halogen atoms.

[0010] Preferably, the general structural formula of the aromatic aldehyde monomer is: , At least one of them, R 3 R 4 R 5 Each atom is independently selected from hydrogen, alkyl, alkoxy, hydroxyl, and halogen atoms; X is independently selected from oxygen, sulfur, and selenium atoms. More preferably, R 3 R 4 R 5 X is a hydrogen atom, and X is a sulfur atom.

[0011] More preferably, the aromatic aldehyde monomer is at least one of 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-dimethylbis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde (BTA) and 5,5'-[1,4-phenylenebis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde (PDA).

[0012] Further, the preparation method of the 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-dimethylbis(acetylene-2,1-dimethyl)]di-m-phthalaldehyde includes:

[0013] The mixture of 5-ethynyl-isophthalaldehyde, 4,7-dibromobenzo[c][1,2,5]thiadiazole, dichlorobis(triphenylphosphine)palladium, cuprous iodide, triethylamine, and N,N-dimethylformamide was stirred and reacted to obtain the final product.

[0014] Furthermore, the molar ratio of 5-ethynyl-isophthalaldehyde, 4,7-dibromobenzo[c][1,2,5]thiadiazole, dichlorobis(triphenylphosphine)palladium, and cuprous iodide is 25~30:10:1~2:5~8.

[0015] Furthermore, the volume ratio of triethylamine to N,N-dimethylformamide is 1~1.5:1.

[0016] Furthermore, the molar ratio of 5-ethynyl-isophthalaldehyde to triethylamine is 1:55~60.

[0017] Furthermore, the temperature of the stirring reaction is 70°C. o C, the time is 48~72 h.

[0018] Further, the preparation method of the 5,5'-[1,4-phenylenebis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde includes:

[0019] The mixture of 5-ethynyl-isophthalaldehyde, 1,4-diiodobenzene, dichlorobis(triphenylphosphine)palladium, cuprous iodide, triethylamine, and N,N-dimethylformamide is stirred and reacted to obtain the final product.

[0020] Furthermore, the molar ratio of 5-ethynyl-isophthalaldehyde, 1,4-diiodobenzene, dichlorobis(triphenylphosphine)palladium, and cuprous iodide is 25~30:10:1~2:5~8.

[0021] Furthermore, the volume ratio of triethylamine to N,N-dimethylformamide is 1~1.5:1.

[0022] Furthermore, the molar ratio of 5-ethynyl-isophthalaldehyde to triethylamine is 1:55~60.

[0023] Furthermore, the temperature of the stirring reaction is 70°C. o C, the time is 48~72 h.

[0024] Preferably, the molar ratio of the aromatic diamine monomer to the aromatic aldehyde monomer is 2:1.

[0025] Furthermore, the Schiff base reaction system also includes a solvent and an acid catalyst.

[0026] Preferably, the solvent is 1,2-dichlorobenzene and 1-butanol or 1,4-dioxane and mesitylene; the acid catalyst is an acetic acid solution.

[0027] Furthermore, the volume ratio of the 1,2-dichlorobenzene, 1-butanol, and acetic acid solution is 8:2:1; the volume ratio of the 1,4-dioxane, mesitylene, and acetic acid solution is 2:8:1.

[0028] Preferably, the Schiff base reaction system is held at a temperature of 120-150°C. o C, the reaction time is 3 to 5 days.

[0029] Beneficial effects

[0030] (1) This invention achieves the precise construction of a two-dimensional alkynyl-imine covalent organic framework by introducing a benzo[c][1,2,5]thiadiazole unit with a strong dipole moment into a two-dimensional alkynyl-imine covalent organic framework material.

[0031] (2) The two-dimensional alkynyl-imine covalent organic framework material constructed in this invention has good crystallinity, enhanced thermal stability and rich functional properties.

[0032] (3) The two-dimensional alkynyl-imine covalent organic framework material provided by the present invention exhibits excellent water vapor adsorption performance and adsorption kinetics characteristics during atmospheric water collection. Attached Figure Description

[0033] Figure 1 The 1H NMR spectrum of 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-dimethylbis(acetylene-2,1-dimethyl)]di-m-phenylenedialdehyde synthesized in Example 1.

[0034] Figure 2 The 1H NMR spectrum of 5,5'-[1,4-phenylenebis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde synthesized in Example 1.

[0035] Figure 3 This is a schematic diagram of the synthetic route for the two-dimensional alkynyl-imine covalent organic framework material of the present invention.

[0036] Figure 4 The Fourier transform infrared spectra of the COF-BB-H material synthesized in Example 2 and its corresponding monomers BTA and BDA are shown.

[0037] Figure 5 The Fourier transform infrared spectra of the COF-PB-H material synthesized in Example 3 and its corresponding monomers PDA and BDA are shown.

[0038] Figure 6 The image shows the powder X-ray diffraction pattern of the COF-BB-H material synthesized in Example 2.

[0039] Figure 7 The image shows the powder X-ray diffraction pattern of the COF-PB-H material synthesized in Example 3.

[0040] Figure 8 The solid-state carbon NMR spectra of the COF-BB-H material synthesized in Example 2 and the COF-PB-H material synthesized in Example 3 are shown.

[0041] Figure 9 The nitrogen adsorption-desorption curve and BET specific surface area (S) of the COF-BB-H material synthesized in Example 2 are shown. BET ).

[0042] Figure 10 The nitrogen adsorption-desorption curve and BET specific surface area (S) of the COF-PB-H material synthesized in Example 3 are shown. BET ).

[0043] Figure 11 (a) is a scanning electron microscope image of the COF-BB-H material synthesized in Example 2.

[0044] Figure 11 (b) is a scanning electron microscope image of the COF-PB-H material synthesized in Example 3.

[0045] Figure 12 (a) is a transmission electron microscope image of the COF-BB-H material in Example 2.

[0046] Figure 12 (b) is a transmission electron microscope image of the COF-PB-H material in Example 3.

[0047] Figure 13 (a) is a water contact angle test diagram of COF-PB-H material in Example 4.

[0048] Figure 13 (b) in the figure is the water contact angle test diagram of the COF-BB-H material in Example 4.

[0049] Figure 14 The two COF materials in Example 5 were at 25 o Isotherm diagram of water vapor adsorption at C.

[0050] Figure 15 The two COF materials in Example 5 were at 40 o Isotherm diagram of water vapor adsorption at C.

[0051] Figure 16 This is an equal-volume adsorption pyrogram of the two COF materials in Example 5.

[0052] Figure 17 The dynamic water vapor adsorption curves of the two COF materials in Example 5 at 20% relative humidity are shown.

[0053] Figure 18 The dynamic water vapor adsorption curves of the two COF materials in Example 5 at 75% relative humidity are shown.

[0054] Figure 19The image shows the powder X-ray diffraction patterns of COF-BB-H in Example 5 before and after soaking in water for 20 days. Detailed Implementation

[0055] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0056] Raw material sources: 5-bromo-m-phenylenedialdehyde (Shanghai Haohong Biomedical Technology Co., Ltd.), ethynyltrimethylsilane (Shanghai Titan Technology Co., Ltd.), 4,7-dibromobenzo[c][1,2,5]thiadiazole (Shanghai Bide Pharmaceutical Technology Co., Ltd.), p-phenylenediamine (BDA, Shanghai Maclean Biochemical Technology Co., Ltd.).

[0057] Example 1

[0058] 5-Bromo-isophthalaldehyde (2.30 g, 10.80 mmol), cuprous iodide (0.08 g, 0.44 mmol), dichlorobis(triphenylphosphine)palladium (0.23 g, 0.33 mmol), and diisopropylamine (12 mL) were added to tetrahydrofuran (25 mL), degassed, and stirred under nitrogen protection. The reaction mixture was pre-stirred at room temperature for 5 min, followed by slow dropwise addition of ethynyltrimethylsilane (11 mL, 77.81 mmol), and the reaction was continued to be stirred at room temperature for 6 h. After the reaction was completed, the reaction solution was concentrated under reduced pressure, and the residue was purified by rapid silica gel column chromatography to give 5-((trimethylsilyl)ethynyl)isophthalaldehyde (1.29 g, 5.60 mmol) as a white powder, with a yield of 52%.

[0059] The obtained 5-((trimethylsilyl)ethynyl)-isophthalaldehyde (1.50 g, 6.50 mmol), potassium carbonate (1.10 g, 7.90 mmol), and methanol (45 mL) were mixed, degassed, and reacted under nitrogen protection at room temperature with stirring for 12 h. After the reaction was completed, water (40 mL) and dichloromethane (45 mL) were added to the reaction system for extraction. The combined organic phases were washed with saturated brine and dried over anhydrous sodium sulfate. The solvent was then removed by rotary evaporation, and the product was dried under vacuum to obtain a white powder of 5-ethynyl-isophthalaldehyde (0.93 g, 5.85 mmol), with a yield of 90%.

[0060] 5-ethynyl-isophthalaldehyde (0.85 g, 5.43 mmol), 4,7-dibromobenzo[c][1,2,5]thiadiazole (0.49 g, 1.66 mmol), dichlorobis(triphenylphosphine)palladium (0.13 g, 0.19 mmol), cuprous iodide (0.16 g, 0.86 mmol), triethylamine (45 mL), and N,N-dimethylformamide (40 mL) were mixed, degassed, and then incubated at 70°C under nitrogen protection. o The reaction was stirred at C for 48 h. After the reaction was completed, the system was cooled to room temperature, and the resulting precipitate was washed successively with methanol and dichloromethane to obtain a bright yellow powder of 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-dimethylbis(acetylene-2,1-dimethyl)]di-m-phthalaldehyde (0.88 g, 1.96 mmol), with a yield of 72%.

[0061] 5-ethynyl-isophthalaldehyde (0.31 g, 1.95 mmol), 1,4-diiodobenzene (0.26 g, 0.79 mmol), dichlorobis(triphenylphosphine)palladium (0.06 g, 0.08 mmol), cuprous iodide (0.07 g, 0.34 mmol), triethylamine (15 mL), and N,N-dimethylformamide (15 mL) were mixed, degassed, and then incubated at 70°C under nitrogen protection. o The reaction mixture was stirred at C for 48 h. After the reaction was complete, water (50 mL) and dichloromethane (45 mL) were added to the reaction system for extraction. The combined organic phases were washed with saturated brine and dried over anhydrous sodium sulfate. The reaction solution was concentrated under reduced pressure, and the residue was purified by rapid silica gel column chromatography to obtain a white powder of 5,5'-[1,4-phenylenebis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde (0.31 g, 0.80 mmol), with a yield of 82%.

[0062] The 1H NMR spectrum of 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-diylbis(acetyl-2,1-diyl)]di-m-phthalaldehyde obtained in this embodiment is as follows: Figure 1 As shown, the 1H NMR spectrum of 5,5'-[1,4-phenylenebis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde is as follows: Figure 2 As shown.

[0063] Example 2

[0064] The 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-diylbis(acetylene-2,1-diyl)]di-m-phthalaldehyde (BTA) of this embodiment was prepared according to Example 1. 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-diylbis(acetylene-2,1-diyl)]di-m-phthalaldehyde (15.0 mg, 0.0334 mmol), p-phenylenediamine (7.3 mg, 0.0668 mmol), n-butanol (0.2 mL), 1,2-dichlorobenzene (0.8 mL), and acetic acid solution (9 mol / L, 0.1 mL) were added to a Schlenk flask (10 mL) and ultrasonically dispersed for 20 min. The flask was then evacuated and backfilled with nitrogen three times, sealed under vacuum, and placed at 120°C. o The reaction was carried out in a constant temperature oven at C for 72 h. After the reaction was completed, the reaction system was cooled to room temperature and filtered. The crude product was washed successively with tetrahydrofuran and n-hexane, and then dried in a vacuum oven for 12 h to obtain orange-yellow COF-BB-H material (16.16 mg), with a yield of 89.9%.

[0065] The infrared spectrum of the COF-BB-H material obtained in this embodiment is as follows: Figure 4 As shown, the PXRD spectrum is as follows Figure 6 As shown, the solid-state carbon NMR spectrum is as follows: Figure 8 As shown, the nitrogen adsorption-desorption curves are as follows: Figure 9 As shown, the scanning electron microscope (SEM) is as follows: Figure 11 As shown in a, the transmission electron microscope (TEM) is as follows: Figure 12 As shown in Figure a, the prepared COF-BB-H material has a hollow fiber morphology, a crystalline framework, a large specific surface area, and good chemical stability.

[0066] Example 3

[0067] The 5,5'-[1,4-phenylenebis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde (PDA) in this example was prepared according to Example 1. 5,5'-[1,4-phenylenebis(acetylene-2,1-diyl)]di-m-phenylenedialdehyde (13.0 mg, 0.0334 mmol), p-phenylenediamine (7.3 mg, 0.0668 mmol), 1,4-dioxane (0.2 mL), mesitylene (0.8 mL), and acetic acid solution (6 mol / L, 0.1 mL) were added to a Schlenk flask (10 mL) and ultrasonically dispersed for 20 min. The flask was then evacuated and backfilled with nitrogen three times, sealed under vacuum, and placed at 120°C. oThe reaction was carried out in a constant temperature oven at C for 72 h. After the reaction was completed, the reaction system was cooled to room temperature and filtered. The crude product was washed successively with tetrahydrofuran and n-hexane, and then dried in a vacuum oven for 12 h to obtain yellow COF-PB-H material (16.20 mg), with a yield of 80.5%.

[0068] The infrared spectrum of the COF-PB-H material obtained in this embodiment is as follows: Figure 5 As shown, the PXRD spectrum is as follows Figure 7 As shown, the solid-state carbon NMR spectrum is as follows: Figure 8 As shown, the nitrogen adsorption-desorption curves are as follows: Figure 10 As shown, the scanning electron microscope (SEM) is as follows: Figure 11 As shown in b, the transmission electron microscope (TEM) is as follows: Figure 12 As shown in b. The results above indicate that the prepared COF-PB-H material has an irregular spherical morphology, a crystalline framework, a large specific surface area, and good chemical stability.

[0069] Example 4

[0070] The COF materials (including COF-BB-H and COF-PB-H materials) after the reaction were subjected to Soxhlet extraction with tetrahydrofuran for 12–20 h. The washed solid powder was then placed at 80 °C. o Dry the COF material in a vacuum oven at C for 10-12 hours. Place the dried COF material into die-casting molds, fill evenly, and then press it to 12 MPa using a manual powder press, holding for 10 minutes. Remove the pressed COF material and place it on a contact angle tester, using water as the test droplet, and record the contact angle data using a CCD camera.

[0071] In this example, the water contact angle test results for COF-PB-H and COF-BB-H materials are shown below. Figure 13 a and Figure 13 b. The results show that the COF-BB-H material has a contact angle close to 0°, exhibiting excellent hydrophilicity; while the COF-PB-H material has a contact angle of 117.6°, exhibiting significant hydrophobicity.

[0072] Example 5

[0073] The obtained COF material powders (including COF-BB-H and COF-PB-H materials) were placed in the degassing system of a fully automated specific surface area and pore structure analyzer, and then subjected to degassing at 100°C. o Vacuum degassing at C for 6 h was followed by helium backfilling to remove residual solvent and moisture. Approximately 10 mg of the dried COF sample was weighed and, using the BELSORP Aqua3 volumetric method, dissolved in 25 °C. o C and 40 oThe water adsorption isotherm of the COF material was determined under C conditions. The isothermal heat of adsorption of the COF material was calculated according to the Clausius-Clapeyron equation.

[0074] Place the dried COF material at 25°C. o Equilibrate for 30 min in a nitrogen atmosphere. Weigh approximately 10 mg of sample and place it in a dynamic water vapor adsorption analyzer at 25°C. o The test was conducted under C conditions; the relative humidity of the humidifying airflow was set to 25% and 70%, and the gas flow rate was 100 mL / min, to obtain the dynamic water vapor adsorption curve of the COF material.

[0075] Place 10 mg of COF-BB-H material in a 10 mL round-bottom flask, add 5 mL of distilled water, and incubate at 25°C. o Stirred at C for 20 days. Filter under reduced pressure, and place the resulting solid powder at 80°C. o Dry in a vacuum oven for 24 hours, then perform powder X-ray diffraction analysis.

[0076] In this embodiment, the COF material is at 25 o C and 40 o The water adsorption isotherms at temperature C are as follows: Figure 14 and Figure 15 As shown, its heat of adsorption is equal to that of adsorption. Figure 16 As shown; the dynamic water adsorption curves under 20% and 75% relative humidity conditions are respectively as follows. Figure 17 and Figure 18 As shown; its X-ray diffraction pattern after immersion in water for 20 days is as follows. Figure 19 As shown in the figure, the results indicate that under the same temperature and humidity conditions, the COF-BB-H material exhibits a higher water adsorption capacity and a faster adsorption rate. Furthermore, the COF-BB-H material demonstrates good water stability and excellent recycling potential during water vapor adsorption.

Claims

1. A two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption, characterized in that, The general structural formula of the material is: Among them, R 1 R 2 R 3 R 4 R 5 All are hydrogen atoms; X is a sulfur atom.

2. A method for preparing a two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption as described in claim 1, characterized in that, Includes the following steps: Aromatic diamine monomers and aromatic aldehyde monomers are reacted via Schiff base reaction to obtain the two-dimensional alkynyl-imine covalent organic framework material for water vapor adsorption.

3. The preparation method according to claim 2, characterized in that: The general structural formula of the aromatic diamine monomer is: R 1 R 2 It is hydrogen.

4. The preparation method according to claim 2, characterized in that: The general structural formula of the aromatic aldehyde monomer is: R 3 R 4 R 5 X is hydrogen; X is a sulfur atom.

5. The preparation method according to claim 4, characterized in that: The aromatic aldehyde monomer is 5,5'-[benzo[c][1,2,5]thiadiazole-4,7-dimethylbis(acetylene-2,1-dimethyl)]di-m-phenylenedialdehyde.

6. The preparation method according to claim 2, characterized in that: The molar ratio of the aromatic diamine monomer to the aromatic aldehyde monomer is 2:

1.

7. The preparation method according to claim 2, characterized in that: The Schiff base reaction system also includes a solvent and an acid catalyst.

8. The preparation method according to claim 7, characterized in that: The solvent is 1,2-dichlorobenzene and 1-butanol; the acid catalyst is an acetic acid solution.

9. The preparation method according to claim 2, characterized in that: The Schiff base reaction system is at a temperature of 120~150°C. o C, the reaction time is 3 to 5 days.

Citation Information

Patent Citations

  • Compound, covalent organic framework material, and preparation methods and applications of compound and covalent organic framework material

    CN111004103A

  • Diyne functionalized covalent organic framework material as well as preparation method and application thereof

    CN120775136A